Keeping quality of betel leaves (Piper betle L.) as influenced by different methods and seasons - A Pariari, M N Imam, (Journal of Spices and Aromatic Crops, 2012)
The objectives of the study were to assess the keeping quality under different seasons and methods of storage to suggest the best method and season for betel leaves storage. In all the treatments, leaves in two forms i.e, petiolated and depetiolated were included. The result showed that December–January i.e, winter season was the best for longer storage of betel leaves in any form and method. Among method of storage, zero energy cool chamber was the best for longest period of storage followed by packing with banana leaves in bamboo basket. Depetiolated condition was always better than petiolated condition for enhancing storage life. Chlorophyll degradation was minimum in petiolated condition either in packing with banana leaves or in treatment with Benzylaminopurine (BA) @ 30 ppm compared to depetiolated condition. Ascorbic acid content was more in sterilized paddy straw packing and in hessian cloth lined with mustard seed and ice pieces compared to other treatments.